Optimization of Keratinase Production By Actinomyces Fradiae 119 and Its Application in Degradation of Keratin Containing Wastes (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of this study was to identify and optimize significant technological parameters influencing keratinolytic enzyme production by A. fradiae 119 and to study its ability to degrade keratin. In the present work chicken feathers meal (CFM) was found to be an excellent substrate for keratinase induction by A. fradiae 119. The strain produced 164 KU/mL keratinolytic activity in basal medium containing 7.5 g/L CFM as the sole source of carbon and nitrogen. Increased keratinolytic activity was achieved in media with ammonium sulfate as nitrogen source, the application of additional nitrogen sources to media containing CFM slightly decreased keratinase synthesis. Optimal parameters of the cultivation process were determined: pH of cultivation medium – 7.2, temperature – 34 ºC and inoculum’s size – 8 %, using the response surface methodology. The yield of keratinase activity was increased by 46 % (267 KU/mL) after optimization of the cultivation process. The good ability of cultural liquid to degrade feathers and wool was detected.